1998
DOI: 10.1002/(sici)1097-4652(199801)174:1<107::aid-jcp12>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Induction of hepatocyte growth factor/scatter factor by interferon-γ in human leukemia cells

Abstract: Induction of hepatocyte growth factor/scatter factor (HGF/SF) may be one of the critical steps in organ regeneration, wound healing, and embryogenesis. We previously reported the production of HGF/SF from various human leukemia cell lines and a high level of the growth factor in blood and bone marrow plasma from patients with various types of leukemia. We determined here the effects of hematopoietic cytokines on HGF/SF production in human leukemia cell lines, KG-1, a myeloid cell line, and RPMI-8226, a B cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The factors that lead to up-regulation of HGF expression in the setting of bleomycin-induced lung injury are beyond the scope of this project, but a variety of proteases and inflammatory cytokines, such as interleukin (IL)-6, IL-1a, IL-1b and TNF-a, have been shown to increase HGF mRNA and protein expression [26][27][28][29][30]. Other data [7] provide an additional variable in persistent HGF production that involves previous exposure to endogenous apoptotic cells or cell debris in lung injury lesions since the phagocytic indexes in BAL alveolar macrophages increased following bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that lead to up-regulation of HGF expression in the setting of bleomycin-induced lung injury are beyond the scope of this project, but a variety of proteases and inflammatory cytokines, such as interleukin (IL)-6, IL-1a, IL-1b and TNF-a, have been shown to increase HGF mRNA and protein expression [26][27][28][29][30]. Other data [7] provide an additional variable in persistent HGF production that involves previous exposure to endogenous apoptotic cells or cell debris in lung injury lesions since the phagocytic indexes in BAL alveolar macrophages increased following bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the active substance in the extract seems to be a non-proteinous macromolecule. Most of the macromolecular inducers of HGF are proteins such as growth factors and cytokines [24,25,27,28,30]. Non-proteinous macromolecular HGF inducers reported so far is heparin which is effective in MRC-5 cells and others [23].…”
Section: Discussionmentioning
confidence: 99%
“…HGF production is induced in response to activation of PKA-and PKC-mediated pathways and is also induced by interleukin-1, tumor necrosis factor-α, interferon-γ, oncostatin-M, heparin, norepinephrine, staurosporine, a scatter factor-inducing factor, and growth factors such as epidermal growth factor (EGF) and platelet-derived growth factor (PDGF) [21][22][23][24][25][26][27][28][29][30]. To date, however, there have been no reports on the effects of plant extracts or juices on HGF production.…”
Section: Introductionmentioning
confidence: 99%
“…The conditioned medium was collected after incubation of the cells for 24 h (PMA-treated human dermal fibroblasts) or 72 h (cholera toxin-treated human dermal fibroblasts, 8-bromo-cAMP-treated human dermal fibroblasts and MRC-5 cells), unless stated otherwise and was frozen at Ϫ30°C for a human HGF ELISA. The sandwich ELISA for human HGF was performed at room temperature as described previously, 38) with a slight modification, 37) except that biotinylated goat anti-human HGF antibody (R&D Systems, Minneapolis, MN, U.S.A.) and horseradish peroxidase-streptavidin conjugate (Zymed Laboratories, San Francisco, CA, U.S.A.) were used as a detection antibody and a horseradish peroxidase conjugate, respectively. HGF levels were expressed as ng/mg cellular protein.…”
Section: Determination Of Hgf Levels In Conditioned Mediamentioning
confidence: 99%
“…21,22,[33][34][35][36] Prompted by the increase in the number of identified modulators for HGF production, we previously examined whether drugs used for the treatment of liver diseases modulate HGF production and HGF induction and reported that interferon (IFN)-g, -a, and -b, which are used for the treatment of tumors and chronic hepatitis C and hepatitis B, are potent inducers of HGF in human leukemia cells. 37) In this study, we found that ursodeoxycholic acid (UDCA), which is widely used for the treatment of chronic cholestatic liver diseases such as primary biliary cirrhosis, strongly inhibited constitutive and induced HGF production in human dermal fibroblasts and MRC-5 cells. The findings suggest that UDCA supplemented with HGF or HGF inducers or agents perturbing the inhibition of HGF production could have a more potential therapeutic effect.…”
mentioning
confidence: 97%